Stimuli-responsive one-dimensional photonic crystals: design, fabrication and sensing. Issue 20 (31st August 2022) - Däntl, Marie; Jiménez-Solano, Alberto; Lotsch, Bettina V.
Abstract : This review gives conceptual insights into stimuli-responsive one-dimensional photonic crystals regarding fabrication, materials, optical properties and sensing principles. Abstract : A wide range of sensors, for example in healthcare, electronics or environmental monitoring, have become indispensable parts of our everyday life and smart sensing technologies, fueled by the Internet of Things, are in high demand. However, most sensors rely on a complex readout as they depend on additional electronics and hence the demand for sensors that can be read out optically with a camera or the naked eye has been growing significantly. Photonic crystals (PCs) and related sensing principles are promising candidates as they are responsive to different stimuli and their readout can be achieved optically. In addition, the properties of PCs can be tailored on-demand so as to meet the users' requirements. In this review, we present an overview of the state-of-the-art of stimuli-responsive PC sensors and delineate how stimuli-responsiveness can be created for desired applications based on optical design and nanoscale fabrication.